Automatic Feature Recognition of Chamfer and Fillet for Turning Part Model by Volume Decomposition Method / Ahmad Faiz Zubair and Mohd Salman Abu Mansor - Zubair, Ahmad Faiz; Abu Mansor, Mohd Salman (Faculty of Mechanical Engineering Universiti Teknologi MARA (UiTM), 2018)
The present paper illustrates the development of generative feature recognition of cylindrical part model that emphasize on recognition of chamfer and fillet.Without automation, manual work on recognizing these features are tedious and time consuming. Chamfers were recognized by conical surface while constant radius fillets on concave and convex edges were recognized by circular faces and edges. Cylindrical stock model, sub-delta volume for finishing (SDVF) of feature's recognized and sub-delta volume for roughing of the part model were generated. The resulted volume decomposition in term of delta volume were then compared with manual calculation of feature's delta volume to achieve the differential error. Two examples of part model were tested and the results show less than zero differential error. These prove that the algorithm is able to recognize cylindrical part model chamfers and fillets feature.